Development and Evaluation of Inclined Plate Metering Mechanism for Carrot Seed - Yadachi, Shiddanagouda; Mani, Indra; Kalra, M S; Kumar, Adarsh; Sahoo, P K (Journal of Agricultural Engineering, 2013)
The ability to place seeds at a given distance apart in a row is an important performance factor of a planter with single seed metering mechanism. Inclined plate seed metering device was developed and evaluated in laboratory for singulation and uniform placement of carrot seeds with different treatment of coating viz. uncoated, biogas slurry coated and thirame coated. Metering device was tested at three inclinations of 40°, 50°and 60° using plates having cells with three shapes viz. triangular, semi-circular and slant cells. Average spacing obtained at the three plate inclinations was 40.4 mm, 50.5 mm and 48.7 mm, respectively. Slant cell metering device inclined at 50° gave best seed spacing with slurry coated and thirame coated seeds. Highest multiple index was obtained at plate inclination of 40° for uncoated seeds, while seed metering by plate with triangular and semi-circular cells showed higher multiples. Slant cell plate with inclination of 50° showed least multiple index of 6.11% with thirame coated seed.The general mean and standard error of quality of feed index were 71.44% and 1.33, respectively. Highest feed index (83.9%)was obtained at plate inclination of 50° with slant type cell shape for thirame coated seed. Highest precision of 20.95% was observed with coefficient of variation of 2.11% at plate inclination of 50 degrees. The selection of plate inclination and type of metering cell for the planter was purely based on average spacing, miss index, multiple index and quality of feed index. Slant type cell plate at inclination of 50° was recommended for sowing of coated seed of carrot.